انعكاسات التنوع اللغوي على المتعلم من منظور المعلم دراسة ميدانية في ابتدائيات مقاطعة المقرن - أديبه ميده; القاده جلول (University of El-Oued جامعة الوادي, 2025)
ملخص: شملت هذه المذكرة ظاهرة من أبرز الظواهر اللغوية، وهي ظاهرة التنوع اللغوي، التي تنعكس في تنوع الأشكال اللغوية المستخدمة من قبل الأفراد للتعبير عن أفكارهم ومشاعرهم. ويُعدّ هذا التنوع انعكاسًا لتراكمات متعددة ومختلفة، تتجلّى في الاستعمال اليومي للغة داخل المجتمع الجزائري، لا سيما في الوسط المدرسي. ومن هذا المنطلق، جاء هذا العمل ليتناول بالدراسة والتحليل تأثير تنوع الأشكال اللغوية داخل المحيط المدرسي على اكتساب المتعلم للغة، انطلاقًا من تصورات المعلمين وتجاربهم. وتهدف هذه الدراسة إلى فهم الكيفية التي ينعكس بها هذا التنوع اللغوي على الأداء اللغوي للمتعلمين، سواء على مستوى الفهم أو الإنتاج، مع محاولة الوقوف على ما إذا كان يمثل عائقًا تربويًا أم فرصة تعليمية ينبغي استثمارها. فقد خُصص المدخل للحديث عن: مفهوم اللغة واللغة الفصحى، وكذا مفهوم العامية واللغة الأم، وأخيرا المرحلة الابتدائية. وقد تناول الفصل الأول الجانب النظري، حيث تم التطرق إلى المفاهيم الأساسية المرتبطة بالتنوع اللغوي، وأسبابه وأشكاله وقضاياه، ثم الوضع اللغوي في الجزائر، وكذا انعكاسات التنوع اللغوي الإيجابية منها والسلبية. أما الفصل الثاني فكان مخصصًا للجانب التطبيقي، حيث وزعنا مجموعة من الاستبيانات تتضمن مجموعة من الأسئلة على عينة تمثلت في معلمي ابتدائيات مقاطعة المقرن (2)، وتم من خلاله عرض وتحليل آراء المعلمين بشأن هذه الظاهرة. وقد كشفت نتائج الدراسة أن التنوع اللغوي له انعكاسات متعددة سلبية وإيجابية على اكتساب اللغة لدى المتعلم، وأكدت في الوقت نفسه أن للمعلم دورًا محوريًا في كيفية توجيه هذا التنوع وتحويله إلى فرصة بيداغوجية تساهم في تحسين الأداء اللغوي لدى المتعلمين. Abstract: This dissertation addressed one of the most prominent linguistic phenomena: linguistic diversity. This phenomenon is reflected in the variety of linguistic forms individuals use to express their thoughts and emotions. Such diversity results from a range of accumulated and varied factors, manifesting in the daily use of language within Algerian society, particularly in the school environment. From this perspective, the present study aims to examine and analyze the impact of the diversity of linguistic forms within the school setting on learners’ language acquisition, based on teachers' perceptions and experiences. The objective of this study is to understand how this linguistic diversity affects learners’ language performance, both in terms of comprehension and production, while also exploring whether it constitutes a pedagogical barrier or an educational opportunity that should be utilized. The introduction was devoted to discussing the concepts of language and Standard Arabic, as well as the notions of colloquial language and the mother tongue, and finally, the stage of primary education. The first chapter dealt with the theoretical framework, covering the key concepts related to linguistic diversity, its causes, forms, and associated issues. It also examined the linguistic situation in Algeria, along with both the positive and negative implications of linguistic diversity. The second chapter was dedicated to the practical aspect of the study. A set of questionnaires was distributed to a sample of primary school teachers from the El-Maqran (2) district. Their responses were analyzed to understand their views on this phenomenon. The study’s findings revealed that linguistic diversity has both negative and positive effects on learners’ language acquisition. They also confirmed that the teacher plays a central role in managing this diversity and transforming it into a pedagogical opportunity that can contribute to improving learners’ linguistic performance.
مذكرة ماستر. لسانيات عامة . 2025.
Keywords: التنوع اللغوي – المتعلم – المعلم – العامية – الفصحى - المرحلة الابتدائية; التنوع اللغوي – المتعلم – المعلم – العامية – الفصحى - المرحلة الابتدائية